Front Cover: Quantum‐Chemical Insight into Self‐Organization of Complex Molecules from Acetylene and Anilines Catalyzed by Superbase KOH/DMSO: One‐Pot Cascade Assembly of 1, 3‐Bis(arylamines) (Asian J. Org. Chem. 4/2023). Issue 4 (3rd April 2023) - Absalyamov, Damir Z.; Vitkovskaya, Nadezhda M.; Orel, Vladimir B.; Schmidt, Elena Yu.; Trofimov, Boris A.
Abstract : The method of one‐pot assembly of 1‐Acetyl‐1, 3‐bis(2‐chloroaniline) is attractive from the point of view of the green chemistry principles: pot‐, atom‐, step‐economical, resource, and energy‐saving procedures using available starting materials and simple catalytic systems. The mechanisms of reactions that proceed sequentially in a superbasic KOH/DMSO medium and form a unique cascade assembly of 1, 3‐diamine from 2‐chloroaniline and acetylene are studied quantum‐chemically. More information can be found in the Research Article by Nadezhda M. Vitkovskaya et al .